Instabilities and nonequilibrium structures V (Nonlinear phenomena and complex systems, 1996)
This volume contains a selection of the lectures given at the Fifth International Workshop on Instabilities and Nonequilibrium Structures, held in Santiago, Chile, in December 1993. The following general subjects are convered: instabilities and pattern formation, stochastic effects in nonlinear systems, nonequilibrium statistical mechanics and granular matter. Review articles on transitions between spatio-temporal patterns and nonlinear wave equations are also included. This book should appeal to physicists and mathematicians working in the areas of nonequilibrium systems, dynamical systems, pattern formation and partial differential equations. Chemists and biologists interested in self-organization and statistical mechanics should also be interested, as well as engineers working in fluid mechanics and materials science.